High-Yielding Soybean: Genetic Gain × Fertilizer Nitrogen Interaction - I. A. Ciampitti; J. Kimball; Eric Adee; O. Ortez; G. I. Carmona (Kansas Agricultural Experiment Station Research Reports, 2016)
The U.S. accounts for 35% of the global soybean production. Potential soybean yields are determined by the interaction of genotype, environment, and management practices (G × E × M). The question “Do high yielding soybean need to be fertilized with nitrogen (N)?” is still a valid one. The overall objective of this project is to study the contribution of N via utilization of varying N strategies under historical and current soybean genotypes. Two field experiments were conducted during the 2015 growing season at Ottawa (east central KS) and at Ashland Bottoms (central KS). Three soybeans varieties were used (1990s = non-RR, 2000s = RR-1, and 2010s = RR-2) under three N systems (non-N applied; late-N, 50 lb N/a; and 550 lb N/a, split in 3 timings) with all seeds inoculated. At Ottawa, the study was planted in an area without soybean history, with yields ranging from 14 to 37 bushels per acre. Superior yields were recorded for the modern soybean variety Roundup Ready (RR-2) relative to the RR-1 and non-RR materials. As related to the N management approach, slightly higher soybean yields occurred when N nutrition was based on fertilizer N application. At the Ashland Bottoms site, yields ranged from 44 to 76 bushels per acre. High yields were with the oldest soybean genotype (non-RR) when N nutrition was based on the fertilizer N application; while low yields were when the N nutrition of the modern soybean variety (RR-2) was based on the inoculation. There was no variety by N factor interaction with yield. The variety (P<0.05) was the main significant single effect, which presented the following order from high to low productivity: non-RR>>RR-1 = RR-2. A conclusion from the first year of this experiment was the field where soybean had not been previously planted (Ottawa) had a lower yield capacity compared to the site with a soybean history (Ashland Bottoms).
Keywords: soybean; nitrogen; inoculation; fertilization; genotypes